Census and nation building in the Brazilian Empire - Botelho, Tarcisio R. (2005)
This article analyses the censuses in XIXth century Brazil, especially in 1852 and in 1872, as a part of the nation building process. I trace a parallel between the necessities of national censuses perceived by the national political elites and the processes of nation and state building. I show that censuses can be considered a part of this process, articulating bureaucratic necessities and symbolic dimensions for the nation building process. In this sense, the Imperial General Census of 1872 exhibited, for the first time, a portrait of the nation, showing the face of Brazilian people and supporting a representation of the nation.